Natural hydraulic lime prepared from industrial solid waste, preparation method and application thereof
By using raw materials such as slag, fly ash and limestone, natural hydraulic lime is prepared, which solves the problems of high production costs and unenvironmental protection in the existing technology, and realizes the high-value utilization of industrial solid waste and natural water High-quality preparation of hard lime.
Patent Information
- Application Number
- CN202410624586.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-05-20
AI Technical Summary
In the prior art, when preparing natural hydraulic lime, natural raw materials are mostly used, resulting in high production costs and unenvironmental protection, and failure to effectively utilize industrial solid waste.
Natural hydraulic lime is prepared by pretreatment, mixing, briquetting, calcining and digestion.
It realizes the high-value utilization of industrial solid waste, reduces production costs, and the prepared natural hydraulic lime complies with BS EN459-2015 standards and is suitable for construction restoration and other applications.
Smart Images

Figure CN118515440B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to natural hydraulic lime prepared from industrial solid waste and a preparation method thereof. Background Art
[0002] Natural hydraulic lime (NHL) is a type of inorganic cementitious material composed of C2S, Ca(OH)2, CaO, CaCO3, SiO2 and a small amount of clay minerals, which is different from traditional lime and cement. It has both hydraulic and gas-hardening properties, and is not a simple preparation and mixture of gas-hardening lime and hydraulic cement. It has strong adhesion, good air permeability, strong self-repairing ability, and good frost resistance and alkali resistance. Since NHL has low hydration heat release and gas-hardening reverse heat release, it avoids internal stress caused by rapid solidification and has good toughness. It is recognized as an energy-saving, environmentally friendly, green and sustainable inorganic cementitious material.
[0003] Compared with lime, NHL is hydraulic, has fast setting speed, good viscosity, strong adhesion, high water resistance and high mechanical strength; compared with cement, NHL is air-hardening, which can make the wall breathable and keep breathing, which is conducive to the exchange of water vapor, and has good frost resistance and alkali resistance, good flexibility, good processability, strong self-repair ability and other characteristics. Due to the low heat release of hydration and air-hardening heat release of NHL, the internal stress caused by rapid solidification is avoided, making it have good toughness. NHL is a traditional binder for masonry mortar, but it is currently produced and used less. Belgium is famous for exporting natural hydraulic lime produced in Tournai. Domestically, it relies on imports and is expensive.
[0004] In foreign countries, natural hydraulic lime can be used to replace cement to prepare decorative mortar and plain concrete, and is widely used in cultural relics protection and ancient building restoration. The hydraulic lime introduced in China is mainly used in the repair and reinforcement of historical buildings, which can eliminate the erosion of sulfate on historical buildings.
[0005] Therefore, in order to prepare natural hydraulic lime, the Chinese patent document with publication number CN115583825A discloses a method for preparing natural hydraulic lime using a composite calcium raw material, a silicon raw material, an admixture and water. The burning stability of natural hydraulic lime is improved, and the early hydration process of natural hydraulic lime is accelerated. The Chinese patent document with publication number CN108863122A discloses a method for obtaining natural hydraulic lime by digesting limestone tailings with water using limestone tailings as raw materials. The Chinese patent document with publication number CN104724953B discloses a method for preparing natural hydraulic lime using limestone and quartz powder. The Chinese patent document with publication number CN113185158A discloses a method for preparing natural hydraulic lime using potassium feldspar and limestone. This invention fills the gap in the preparation of NHL3.5 hydraulic lime in my country. The Chinese patent document with publication number CN116924701A discloses a method for preparing natural hydraulic lime using diatomaceous earth and lime. The invention produces various types of lime by controlling the content of diatomaceous earth and roasting conditions.
[0006] The above-mentioned method for producing natural hydraulic lime mostly uses natural raw materials for production, and does not use industrial solid waste such as slag, so the production cost is high and it is not environmentally friendly.
[0007] In order to respond to my country's environmental protection policies, technical personnel in this field are committed to developing a natural hydraulic lime prepared from industrial solid waste and a preparation method. Summary of the invention
[0008] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a natural hydraulic lime prepared by using industrial solid waste and a preparation method thereof.
[0009] To achieve the above object, the present invention provides a natural hydraulic lime prepared from industrial solid waste, comprising the following raw materials by mass fraction: 50% to 85% limestone, 10% to 20% slag, 5% to 20% silica fume and 5% to 20% fly ash.
[0010] The present invention also provides a method for preparing the above-mentioned natural hydraulic lime, which is characterized by comprising the following steps:
[0011] (1) Raw material pretreatment: crushing and grinding limestone into limestone powder with a particle size of 0.074 mm and a sieve residue mass percentage of no more than 3%; sieving silica fume;
[0012] (2) Mixing and briquetting: Mix limestone powder, slag, fly ash and sieved silica fume for 2 to 3 hours, and finally press the mixed powder into round cakes.
[0013] (3) Calcination of test blocks: The round cakes are placed in a muffle furnace and calcined into test blocks at a calcination temperature of 950° C. to 1150° C.
[0014] (4) Clinker digestion: Grind the calcined test blocks into calcined powder, and finally add water to digest the calcined powder.
[0015] Furthermore, the size of the round cake is Φ100×30mm.
[0016] Furthermore, the calcination in step (3) includes: heating to 850°C at 10°C / min, keeping the temperature for 90 minutes, then heating to 950°C-1150°C at 10°C / min, keeping the temperature for 0.5 hours, and then naturally cooling to room temperature.
[0017] Furthermore, the calcined powder is digested with water in step (4) including: the mass ratio of calcined powder to water is 1:1, and then digested at a stirring rate of 600 to 900 rpm, and the digestion time is 2 min.
[0018] Furthermore, after step (4), there is step (5) of drying and grinding: the drying temperature is 75° C., the drying time is 12 hours, and the mixture is ground into powder after drying.
[0019] The present invention also provides an application of the above-mentioned natural hydraulic lime, which is applied to repairing brick walls. The natural hydraulic lime and standard sand are mixed into mortar with a mass ratio of 1:3 and a water-cement ratio of 0.6, and the mortar is used to repair brick walls.
[0020] The mineral phase composition of slag is a glass phase structure rich in SiO2 and CaO. The glass structure of slag is also related to its own chemical element composition. The main chemical composition of slag is SiO2, Al2O3, CaO and MgO. The physical properties and chemical composition of slag determine the reactivity of slag to a certain extent. At the same time, slag contains calcium and silicon raw materials required for the preparation of natural hydraulic lime. Using slag in the preparation of natural hydraulic lime can reduce the use of limestone and make rational use of industrial solid waste.
[0021] Slag is a by-product of the blast furnace ironmaking process. During the ironmaking process, iron oxide is reduced to metallic iron at high temperatures, and impurities such as silica and alumina in the iron ore react with lime to form a molten material with silicates and aluminosilicates as the main components, which is quenched into loose, porous granules. For every ton of pig iron smelted in China, about 0.4 tons of slag is produced. The amount of slag is large, and the irrational use of slag will lead to many environmental problems and cause soil, surface water and groundwater pollution. In order to create better economic and environmental benefits, it is very necessary to reuse slag.
[0022] Fly ash is the fine ash collected from the flue gas after coal combustion, and is the main solid waste discharged from coal-fired power plants. The main sources of fly ash are thermal power plants and urban central heating boilers that use pulverized coal as fuel. Fly ash pollutes the environment and is dangerous to human health. Fly ash contains siliceous raw materials and can be used to prepare natural hydraulic lime, which plays a role in recycling waste.
[0023] Improper mining or utilization of limestone mines may cause environmental pollution or ecological damage. In order to consider environmental protection and sustainable development, the use of calcium industrial solid waste can reduce the mining of limestone, play a role in waste utilization, make high-value utilization of waste residues, and reduce environmental pollution caused by the accumulation of industrial solid waste.
[0024] According to European BS EN-459 and BS EN-196 standards, natural hydraulic lime is divided into NHL2, NHL3.5 and NHL5. The numbers refer to the hydraulic index of natural hydraulic lime, which refers to the compressive strength. This strength is generally based on European standards, according to a certain ratio of lime and sand, and is mixed into a mixed mortar. After a drying period of 28 days, the minimum compressive strength is measured. The compressive strength of NHL2 is low, the compressive strength of NHL3.5 is medium, and the compressive strength of NHL5 is high.
[0025] Regarding the optimal calcination temperature range for producing natural hydraulic lime, domestic and foreign scholars have concluded through experimental methods that lower temperatures will lead to the formation of an amorphous phase, and higher calcination temperatures will result in lower reactivity of dicalcium silicate and less digestion residue. The most suitable temperature is in the range of 1000-1100°C.
[0026] The beneficial effects of the present invention are as follows: the natural hydraulic lime prepared by industrial solid waste and the preparation method of the present invention include the following raw materials by mass fraction: 50% to 85% limestone, 10% to 20% slag, 5% to 20% silica fume and 5% to 20% fly ash. A large amount of industrial waste fly ash, slag and limestone are used as raw materials to prepare natural hydraulic lime, and the raw materials are designed in proportion. The mixed powder blocks are calcined and then digested with water to obtain natural hydraulic lime; it is economical and environmentally friendly, realizes the reuse of solid waste, effectively reduces production costs, and protects the ecological environment; and after raw material pretreatment, calcination and digestion processes, natural hydraulic lime that meets the BS.EN459-2015 standard is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD pattern after digestion of Example 1
[0028] Figure 2 XRD pattern after digestion of Example 3
[0029] Figure 3This is a photo of a brick wall being repaired using the natural hydraulic lime mortar prepared in Example 1.
[0030] Figure 4 This is a photograph of a 28-day pull-out test conducted after the brick wall was repaired using Example 1. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, may be combined in any manner and, unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes, that is, unless otherwise stated, each feature is merely one embodiment of a series of equivalent or similar features.
[0033] In the following examples, the slag is abrasive blast furnace slag powder, which is S95-GGBFS powder produced by Hengle New Building Materials Co., Ltd., and the silica fume is produced by Huashen Intelligent Technology Co., Ltd.
[0034] Example 1
[0035] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 53.2% limestone, 13.4% slag, 20% silica fume and 13.4% fly ash. The preparation process includes the following steps:
[0036] (1) Raw material pretreatment: The raw materials are composed of limestone, abrasive blast furnace slag powder, fly ash and silica fume. First, the limestone is crushed and ground into limestone powder with a particle size of 0.074 mm and a sieve residue of no more than 3%. The silica fume is sieved. Since the median particle sizes of slag powder and fly ash are fine enough, no further sieving is required.
[0037] (2) Mixing and briquetting: limestone powder, slag, fly ash and sieved silica fume are mixed for 3 hours, and finally the mixed powder is pressed into round cakes with a size of Φ100×30 mm.
[0038] (3) Calcination of test blocks: The round cakes were placed in a muffle furnace and calcined into test blocks at a calcination temperature of 950°C to 1150°C. Specifically, the temperature was increased to 850°C at a rate of 10°C / min, kept at that temperature for 90 min, then increased to 1150°C at a rate of 10°C / min, kept at that temperature for 0.5 h, and then naturally cooled to room temperature.
[0039] (4) Clinker digestion: The calcined test block was ground into calcined powder, and finally the calcined powder was digested with water. Specifically, the calcined powder was digested with water, the mass ratio of calcined powder to water was 1:1, and then the digestion was carried out at a stirring rate of 600 rpm and a digestion time of 2 min.
[0040] (5) Drying and grinding: The drying temperature is 75°C and the drying time is 12 h. After drying, the mixture is ground into powder.
[0041] Example 2
[0042] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 51.6% limestone, 15% slag, 20% silica fume and 13.4% fly ash. The preparation process includes the following steps:
[0043] (1) Raw material pretreatment: The raw materials are composed of limestone, abrasive blast furnace slag powder, fly ash and silica fume. First, the limestone is crushed and ground into limestone powder with a particle size of 0.074 mm and a sieve residue of no more than 3%. The silica fume is sieved. Since the median particle sizes of slag powder and fly ash are fine enough, no further sieving is required.
[0044] (2) Mixing and briquetting: limestone powder, slag, fly ash and sieved silica fume are mixed for 2 hours, and the mixed powder is finally pressed into round cakes with a size of Φ100×30 mm.
[0045] (3) Calcination of test blocks: The round cakes were placed in a muffle furnace and calcined into test blocks at a calcination temperature of 950°C to 1150°C. Specifically, the temperature was increased to 850°C at a rate of 10°C / min, kept at that temperature for 90 min, then increased to 1000°C at a rate of 10°C / min, kept at that temperature for 0.5 h, and then naturally cooled to room temperature.
[0046] (4) Clinker digestion: The calcined test block was ground into calcined powder, and finally the calcined powder was digested with water. Specifically, the calcined powder was digested with water, the mass ratio of calcined powder to water was 1:1, and then the digestion was carried out at a stirring rate of 800 rpm for 2 min.
[0047] (5) Drying and grinding: The drying temperature is 75°C and the drying time is 12 h. After drying, the mixture is ground into powder.
[0048] Example 3
[0049] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 73.2% lime, 13.4% slag, 6.7% silica fume and 6.7% fly ash. The preparation process includes the following steps:
[0050] (1) Raw material pretreatment: The raw materials are composed of limestone, abrasive blast furnace slag powder, fly ash and silica fume. First, the limestone is crushed and ground into limestone powder with a particle size of 0.074 mm and a sieve residue of no more than 3%. The silica fume is sieved. Since the median particle sizes of slag powder and fly ash are fine enough, no further sieving is required.
[0051] (2) Mixing and briquetting: limestone powder, slag, fly ash and sieved silica fume are mixed for 3 hours, and finally the mixed powder is pressed into round cakes with a size of Φ100×30 mm.
[0052] (3) Calcination of test blocks: The round cakes were placed in a muffle furnace and calcined into test blocks at a calcination temperature of 950°C to 1150°C. Specifically, the temperature was increased to 850°C at a rate of 10°C / min, kept at that temperature for 90 min, then increased to 950°C at a rate of 10°C / min, kept at that temperature for 0.5 h, and then naturally cooled to room temperature.
[0053] (4) Clinker digestion: The calcined test block was ground into calcined powder, and finally the calcined powder was digested with water. Specifically, the calcined powder was digested with water, the mass ratio of calcined powder to water was 1:1, and then the digestion was carried out at a stirring rate of 900 rpm and a digestion time of 2 min.
[0054] (5) Drying and grinding: The drying temperature is 75°C and the drying time is 12 h. After drying, the mixture is ground into powder.
[0055] Example 4
[0056] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 53.3% lime, 13.3% slag, 13.7% silica fume and 19.6% fly ash. The preparation process includes the following steps:
[0057] (1) Raw material pretreatment: The raw materials are composed of limestone, abrasive blast furnace slag powder, fly ash and silica fume. First, the limestone is crushed and ground into limestone powder with a particle size of 0.074 mm and a sieve residue of no more than 3%. The silica fume is sieved. Since the median particle sizes of slag powder and fly ash are fine enough, no further sieving is required.
[0058] (2) Mixing and briquetting: limestone powder, slag, fly ash and sieved silica fume are mixed for 3 hours, and finally the mixed powder is pressed into round cakes with a size of Φ100×30 mm.
[0059] (3) Calcination of test blocks: The round cakes were placed in a muffle furnace and calcined into test blocks at a calcination temperature of 950°C to 1150°C. Specifically, the temperature was increased to 850°C at a rate of 10°C / min, kept at that temperature for 90 min, then increased to 950°C at a rate of 10°C / min, kept at that temperature for 0.5 h, and then naturally cooled to room temperature.
[0060] (4) Clinker digestion: The calcined test block was ground into calcined powder, and finally the calcined powder was digested with water. Specifically, the calcined powder was digested with water, the mass ratio of calcined powder to water was 1:1, and then the digestion was carried out at a stirring rate of 900 rpm and a digestion time of 2 min.
[0061] (5) Drying and grinding: The drying temperature is 75°C and the drying time is 12 h. After drying, the mixture is ground into powder.
[0062] Example 5
[0063] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 70% lime, 10% slag, 10% silica fume and 10% fly ash. The steps in the preparation are the same as those in Example 4 and will not be repeated here.
[0064] Example 6
[0065] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass: 60% lime, 13.4% slag, 19.6% silica fume and 7% fly ash. The steps in the preparation are the same as those in Example 4 and will not be repeated here.
[0066] Example 7
[0067] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 60% lime, 13.4% slag, 7% silica fume and 19.6% fly ash. The steps in the preparation are the same as those in Example 4 and will not be repeated here.
[0068] Example 8
[0069] A natural hydraulic lime prepared from industrial solid waste includes the following raw materials by mass fraction: 55% lime, 10% slag, 20% silica fume and 15% fly ash. The steps in the preparation are the same as those in Example 4 and will not be repeated here.
[0070] The comparative example is brick powder BP-10 sold commercially by a certain company.
[0071] The mortars prepared in the above 8 embodiments and comparative examples were tested for compressive and flexural strength. The above 8 embodiments and comparative examples were respectively prepared into mortars with a mass ratio of 1:3 and a water-cement ratio of 0.6 with standard sand. The mortars were poured into iron molds for molding. The molded samples were demolded after 36 hours. The samples were cured for 28 days and finally tested for compressive and flexural strength.
[0072] The compressive strength measured after curing the sample for 28 days meets the strength requirement of NHL2 in BS EN459-1:2015. The present invention uses industrial solid waste to prepare natural hydraulic lime, which makes high-value use of industrial solid waste and is applied to the repair of the exterior wall of masonry walls of historical buildings.
[0073] The test results are shown in the following table:
[0074]
[0075] It can be seen from the experimental results in the above table that, compared with the comparative example, the eight embodiments in the present technical solution have higher compressive strength and flexural strength and shortened setting time, and the compressive strength meets the strength requirements of NHL2 in the BS EN459-1:2015 specification.
[0076] The chemical structures of Example 1 and Example 3 were analyzed by X-ray diffraction. Figure 1 As shown, the natural hydraulic lime of Example 1 contains C2S, Ca(OH)2, Al(OH)3 and C3S, such as Figure 2 The natural hydraulic lime of Example 3 shown contains C2S, Ca(OH)2 and Al(OH)3.
[0077] In addition, Figure 3 , Figure 4 As shown, the natural hydraulic lime of Example 1 and standard sand are prepared into mortar with a mass ratio of 1:1 and a water-cement ratio of 0.6. The mortar is used to repair the brick wall. The repaired brick wall is subjected to a 28d pull-out test, and the bonding strength is 0.377MPa, which is greater than the NHL 28d pull-out test standard requirement.
[0078] The present invention provides the preferred specific embodiments of the present invention described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A natural hydraulic lime prepared from industrial solid waste, characterized in that: The raw materials include the following mass fractions: limestone 50% to 85%, slag 10% to 20%, silica fume 5% to 20% and fly ash 5% to 20%; The preparation method comprises the following steps: (1) Raw material pretreatment: crushing and grinding limestone into limestone powder with a particle size of 0.074 mm and a sieve residue mass percentage of no more than 3%; sieving silica fume; (2) Mixing and briquetting: Mix limestone powder, slag, fly ash and sieved silica fume for 2 to 3 hours, and finally press the mixed powder into round cakes; (3) Calcination of test blocks: The round cakes were placed in a muffle furnace for calcination into test blocks, the temperature was raised to 850° C. at 10° C. / min, kept at that temperature for 90 min, then the temperature was raised to 950° C. to 1150° C. at 10° C. / min, kept at that temperature for 0.5 h, and then naturally cooled to room temperature; (4) Clinker digestion: Grind the calcined test blocks into calcined powder, and finally add water to digest the calcined powder.
2. The natural hydraulic lime according to claim 1, characterized in that: The size of the round cake is Φ100×30mm.
3. The natural hydraulic lime according to claim 1, characterized in that: The step (4) of adding water to the calcined powder for digestion includes: the mass ratio of the calcined powder to water is 1:1, and then digesting at a stirring rate of 600 to 900 rpm for a digestion time of 2 minutes.
4. The natural hydraulic lime according to claim 1, characterized in that: After step (4), there is step (5) of drying and grinding: the drying temperature is 75° C., the drying time is 12 hours, and the powder is ground after drying.
5. A use of the natural hydraulic lime as claimed in claim 1, characterized in that: The invention is applied to repairing brick walls, wherein the natural hydraulic lime and standard sand are mixed into mortar with a mass ratio of 1:1 and a water-cement ratio of 0.6, and the mortar is used to repair brick walls.
Citation Information
Patent Citations
A kind of method that utilizes limestone and quartz powder to prepare natural hydraulic lime
CN104724953B
Natural hydraulic lime and preparation method thereof
CN108863122A
Method for preparing natural hydraulic lime from potassium feldspar and limestone
CN113185158A
Hydraulic lime as well as preparation method and application thereof
CN116924701A
Molded article using hydraulic lime and method for producing same
CN110461556A